Identifying Capacities an Extension Network May Need to Effectively Support the Professionalization of Extension Providers - Kevan W. Lamm; Alexa J. Lamm; Kristin Davis; B. Jyothi Swaroop; Leslie D. Edgar (Journal of International Agricultural and Extension Education, 2020)
Professionalization is a critical component of organizational capacity and productivity. Yet, rural advisory service (RAS) providers who are charged with disseminating research-driven techniques and ideas that enhance agricultural production and addressing local stakeholder needs are often overlooked in this area.One of the critical disconnects is the lack of consistent capacities for RAS networks to effectively support the professionalization of RAS providers. Based on a framework analyzing the typical milestones associated with professionalization efforts, capacity building, and social capital the study provides insights into the support mechanism needed for professionalization. Specifically, a Delphi a panel of 31 experts from 24 countries arrived at consensus on 33 specific capacitiesa RAS network may need to effectively support the professionalization of RAS providers. The results of the research provide a practical framework for RAS networks to consider from a professionalization and capacity building perspective.
Keywords: professionalization; delphi; evaluation; capacity assessment; extension; network